SUBMISSION OF THE ADDITIONAL REPORT TO THE AUDIT COMMITTEE - Карпачова, Ольга (Socio-economic relations in the digital society, 2019)
The preparation and submission by the auditor of an additional report to the audit committee is a relatively new concept and task for Ukrainian subjects of audit activity. One of the main problems in drawing up an additional report is that the subjects of audit activity in Ukraine were not ready for such a report. Therefore, it is not surprising that in the first year, when the Law of Ukraine of December 21, 2017 № 2258-VIII «On the Audit of Financial Statements and Auditing Activities» demanded such a report from auditors, most of the auditors did not compile it correctly. The methodology for reporting in accordance with International auditing standards and Ukrainian legislation will always be an urgent issue for audit entities. The Audit Committee is one of the most important supervisory bodies in the enterprise. It is a so-called entity’s financial management tool. In accordance with the law, an additional report for the audit committee is prepared in the manner specified for the preparation of the audit report. However, it is important that the supplementary report is submitted no later than the date of submission of the audit report. In accordance with the law, an additional report for the audit committee is prepared in the manner specified for the preparation of the audit report.First of all, it should be noted that this report forms part of a continuous communication process in accordance with the requirements of International Audit Standard 260 «Communication with Those Charged with Governance». This report is important evidence of compliance with ISA 260. This article discusses the history of the creation of the audit committee. The relevance of compiling an additional report for the audit committee is determined. The requirements for the preparation of an additional report in accordance with the current legislation of Ukraine and international audit standards are analyzed. The errors of the subject of audit activity in the preparation of an additional report are analyzed. Recommendations on the prevention of errors in the preparation of an additional report for the audit committee were formed and proposed.
Keywords: audit; auditor’s report; an additional report; audit committee; working documents; large enterprises; enterprises of public interest